Multiple scattering effect on luminescence properties of organic luminophors - Tikhonov, E.; Yashchuk, V.P.; Prygodyuk, O.; Bezrodny, V.; Filatov, Yu. (Functional Materials, 2004)
Luminescence properties of the multiple-scattering rhodamina 6 G solutions in solid polymers as functions of scattering efficiency and sample thickness have been investigated. It was found that luminescence spectrum (LS) as well as integrated (over the spectrum) intensity observed in the direction backward to the excitation beam depend significantly on the scattering efficiency being varied using changes of the concentration and refractive index of the embedded scattering microparticles. The integrated intensit y increases with the particle concentration increase. This increasing is due to spatial red is-tribution of luminescence radiation when being multiply scattered in the sample as well as to additional absorption of the excitation light. The LS dependence on the scattering efficiency is caused by reabsorption of the luminescence radiation in the sample. Thus, varying the reabsorption allows tuning the LS maximum over the 20 nm range. Two possible methods of the LS tuning using the sample thickness and scattering efficiency variations were investigated. The second tuning method is preferable because energy efficiency of the sample remains unchanged. Исследованы люминесцентные свойства многократно рассеивающих полимерных растворов красителя родамина 6Ж в зависимости от эффективности рассеяния и толщины образца. Установлено, что спектр люминесценции (СЛ) и интегральная (по спектру) интенсивность люминесценции, наблюдаемые в направлении "на отражение" относительно пучка возбуждения, существенно зависят от эффективности рассеяния, которая варьировалась изменением концентрации и показателя преломления рассеивающих частиц. Интегральная интенсивность возрастает при увеличении концентрации частиц, что обусловлено пространственным распределением излучения люминесценции вследствие рассеяния и возникновением дополнительного поглощения возбуждающего света. Зависимость СЛ от эффективности рассеяния обусловлена перепоглощением излучения люминесценции. Изменение перепоглощения позволяет плавно перестраивать максимум СЛ в пределах 20 нм. Исследованы два метода перестройки СЛ путем изменения толщины образца и эффективности рассеяния. Преимуществом второго метода перестройки есть постоянство энергетической эффективности образца в процессе перестройки. Досліджувались люмінєсцєнтні властивості багатократно розсіювальних полімєрних розчинів родаміну 6Ж. Встановлено, що спектр люмінесценції (СЛ) та інтегральна (по спектру) інтенсивність люмінесценції, при використаній геометрії спостереження "на відбиття", суттєво залежать від ефективності розсіяння, котра варіювалась зміною концентрації та показника заломлення частинок. Інтегральна енергія зростає при зростанні концентрації розсіювальних частинок, що обумовлено просторовим перерозподілом випромінення люмінесценції внаслідок розсіяння та виникненням додаткового поглинання випромінення збудження. Залежність СЛ від ефективності розсіяння обумовлена перепоглинанням випромінення люмінесценції у зразку. Це дозволяє реалізувати плавну перестроювання СЛ шляхом зміни ефективності перепоглинання. Досліджено два методи такого перестроювання СЛ шляхом варіювання товщини зразка та ефективності розсіяння. Перевагою другого методу є незмінність енергетичної ефективності зразка.